Structural and catalytic properties of the peroxygenase P450 enzyme CYP152K6 from Bacillus methanolicus - Girvan, Hazel M. (J Inorg Biochem, 2018)
The CYP152 family of cytochrome P450 enzymes (P450s or CYPs) are bacterial peroxygenases that use hydrogen peroxide to drive hydroxylation and decarboxylation of fatty acid substrates. We have expressed and purified a novel CYP152 family member – CYP152K6 from the methylotroph Bacillus methanolicus MGA3. CYP152K6 was characterized using spectroscopic, analytical and structural methods. CYP152K6, like its peroxygenase counterpart P450(SPα) (CYP152B1) from Sphingomonas paucimobilis, does not undergo significant fatty acid-induced perturbation to the heme spectrum, with the exception of a minor Soret shift observed on binding dodecanoic acid. However, CYP152K6 purified from an E. coli expression system was crystallized and its structure was determined to 1.3 Å with tetradecanoic acid bound. No lipids were present in conditions used for crystallogenesis, and thus CYP152K6 must form a complex by incorporating the fatty acid from E. coli cells. Turnover studies with dodecanoic acid revealed several products, with 2-hydroxydodecanoic acid as the major product and much smaller quantities of 3-hydroxydodecanoic acid. Secondary turnover products were undec-1-en-1-ol, 2-hydroxydodec-2-enoic acid and 2,3-dihydroxydodecanoic acid. This is the first report of a 2,3-hydroxylated fatty acid product made by a peroxygenase P450, with the dihydroxylated product formed by CYP152K6-catalyzed 3-hydroxylation of 2-hydroxydodecanoic acid, but not by 2-hydroxylation of 3-hydroxydodecanoic acid.